Mediation in criminal proceedings: novelties of legislation and prospects for its improvement - T. H. Fomina (Law and Safety)
The article highlights the problematic issues of the use of mediation in criminal proceedings in Ukraine, as well as formulates proposals for their solution. The leading trend in the development of modern legal systems is the use of alternative means of resolving criminal disputes, including mediation. Ukraine is guided in this direction by the international legal standards and the positive experience of many foreign countries. In the general sense, mediation contributes to the humanization of criminal policy against the offender, creates conditions for ensuring the rights, freedoms and legitimate interests of the victim and real compensation for the damage caused to them, accelerates the criminal process. The concept of mediation in criminal proceedings is given. It is stated that the long path of Ukraine to the standardization of mediation was successful on November 16, 2021 in connection with the adoption of the Law of Ukraine “On Mediation” № 1875-IX. Instead, introducing the possibility of mediation in criminal proceedings, the legislator generally avoided amending the CPC of Ukraine, in particular to determine the status of mediator, establishing the boundaries of mediation of criminal conflicts, formulating the peculiarities of its conduct in criminal proceedings. As a reaction to the shortcomings of the legal regulations, it is proposed: first, to amend paragraph 25 of Part 1 of Art. 3 of the CPC of Ukraine, where a mediator should be identified among the participants in the criminal proceedings; secondly, to define in a separate article of the CPC of Ukraine the concept of mediator, their rights and obligations, in connection with which the author’s position on this issue is expressed. The limits of mediation of criminal disputes at the legislative level are not set. It has been proved that the legal basis for mediation in criminal proceedings may be the provisions of the CPC of Ukraine on criminal proceedings under agreements, as well as the provisions of the Criminal Code of Ukraine on release from criminal liability in connection with reconciling the perpetrator with the victim. In Ukraine, a pilot project on the use of restorative procedures in criminal proceedings against minors has been implemented since 2019. Positive examples of this project have shown that the mediation procedure has clear advantages over punitive justice.